The Use of ECMO in Acute Respiratory Failure: Analysis of Advantages, Clinical Challenges, and Long-Term Outcomes in Critically III Patients - Manzano Gallegos, Lisset Alexandra; Castro Romero, Oswaldo Sócrates; Zapa Cedeño, Juliana Karina; Zambrano Vanegas, María José; Azua Sandoya, Lady Yackeline; Villarroel Guevara, Mauricio Antonio (Journal of Neonatal Surgery, 2025)
A systematic review was conducted on the production and publication of studies related to the use of ECMO, acute respiratory failure, clinical challenges, and the management of critically ill patients, covering the period from 2020 to 2023 and using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. The objective of this analysis was to identify the main characteristics of the publications registered in the Scopus and WoS databases, as well as to evaluate their contribution to the study of the variables raised. In a first phase, a total of 61 publications were identified. Subsequently, the search was refined by introducing keywords on both platforms, such as digital strategies, ICT, education and Latin America, which allowed the sample to be reduced to 24 documents, after the exclusion of duplicates and those that did not meet the inclusion criteria. Among the most relevant findings, it is highlighted that the use of ECMO in the management of acute respiratory failure has proven to be fundamental, especially during the COVID-19 pandemic, where it has been crucial to improve the survival of critically ill patients with acute respiratory distress syndrome.